Up close 4 - Diaz, Isobel Rainey de (Heinle & Heinle, 2002)
Features spiraled approach to language learning - presentation, reinforcement, and expansion of communication forms and structures - that promotes the gradual but secure development of the listening, speaking, reading, and writing skills required in beginning through intermediate programs